Relationship between Architect Hajeedar's Design Ideology and Sustainable Design Characteristics in Mosque Building - Mohd Siraj, Suhailah M; Yusof , Hanita; Aziz, Nurul Syaheera; Elgadi, Ahmed A. (International Journal of Sustainable Construction Engineering and Technology, 2022)
Hajeedar is one of the prominent architects in Malaysia who is well-known for his personality, forward-thinking and modern-minded while remaining proud of Malay tradition and religious beliefs. Many of his architectural design ideology revolve around the context and material of the building. This is to ensure that the building is comfort, sustain and used by the community in the surrounding area. The objective of this study is to determine the relationship between architect Hajeedar's design ideology and the sustainable design characteristics of site development, indoor quality, material selection, and energy efficiency. The data for this study was obtained through an interview with architect Hajeedar, literature review on sustainable design characteristic and observation on the selected mosque building. Finding shows that there is similarity of Hajeedar’s design ideology and sustainable design characteristics which can be seen in the mosque design. This study is to provide understanding of the relationship between architect Hajeedar’s design ideology and sustainable design characteristics which influenced the architecture of mosque design.